Feasibility comparison of options constructive schemes of monolithic frame buildings - Utelbay Куат (Рroblems of engineering and professional education, 2023)
This article deals with a comprehensive study of constructive schemes of the monolithic frame buildings by the technical and economic indicators. There were 5 options analyzed, and as a result of mathematical modeling in software complex «MONOMAH", determined that the different arrangement of the frame elements in the design scheme of the building affects the consumption of materials, and, respectively, at the value of the object. There were identified most and least efficient constructive schemes of the buildings.